GEOLOGICAL POSITION AND ORE-BEARANCE OF GRANITOID BELTS IN THE GREAT ALTAI - Diachkov, B.; Mataybaeva, I.; Chernenko, Z.; Teut, E. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Redeveloping national mineral resource base of rare metals is a burning issue for East Kazakhstan. This primarily concerns tantalum, beryllium and niobium, for their being widely used in HT. Technological improvements and developments have become vital for metallogenic forecasting and study in the Republic of Kazakhstan, as there arises a need to provide a scientific basis for the replacement of national resources in general. Based on a theory of drift, this paper discusses some genetic types of gold-bearing and rare-metal deposits relative to the nature of granitoid belts, their origin and distribution in the orogenic post-collision stage of activation, their geotectonic position, etc. In the Mine Altai payable pyrite-gold-copperpolymetallic deposits originated in rift geodynamics; they are flanked by volcanic basalt-andesite-rhyolite arcs and occur in the Devonian volcanicsedimentary sequence. True gold-ore deposits of quartz-veined and quartz-gold-sulfide-carbon types originated during the collisional geodynamics of Kazakhstan and the Mine Altai microcontinents. These bodies are genetically connected with a system of volcanic-plutonic formations and small intrusions of Middle-Upper Carboniferous gabbro, diorite, granodiorite, and plagiogranite (Bakyrchyk, Bolshevik, Suzdal, etc.). In the post-collision orogenic stage of inner-plate activation (P1-T1) there were localized large granitoid belts of normal and high alkalinity (Kalba-Narym, the Mine Altai, Akbyyik-Akzhaylyausk, etc.). They are rare-metal bearing (Ta, Nb, Be, Li, Sn, W, Mo) and rare-earth bearing (Nb-Zr-RE) specializations (mineralizations of Bakennoe, Yubileinoe, Verhnee Espe etc.). Residuum deposits of nickel-cobalt, zirconium-titanium and gold (Belohorskoe, Karaotkel, Zhanan etc.) refer to the Cimmerian cycle of continental rifting. The metallogenic specialization identified in the given geodynamics lays the foundation for further forecasting and developing new minerilazitions.